Krisis Identitas dan Sosial Budaya di Kota Industri: Studi Terhadap Pekerja di Jakarta dan Makassar, Indonesia - Drajat Tri Kartono; Ahmad Zuber; Atik Catur Budi; Panggio Restu Wilujeng (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
When it relates to national identity, the issue of identity becomes relevant in the era of globalization. Considering the distance between local, national, and global identities and the variables involved is crucial. This research aims to find the construction of national identity within globalization exposure, socio-cultural changes, and formulation of Excel identity. This research took place in Jakarta and Makasar. This research used grounded theory as its approach. The data are collected using observation, interview, and Focus Group Discussion with snowball sampling. The research results show that the construction of national identity is blended in which national identity is mixed with local and global ones. Also, socio-cultural change influences the construction of identity. Forming a superior identity is equally vital to one’s international, national, and regional identity.